Diffuse interface method for fluid flow and heat transfer in cellular solids. (September 2015) - Ettrich, J.; Nestler, B.
Highlights: Diffuse interface method for heat and mass transfer simulation of cellular solids. Method for realistic modelling of complex microscale structures of cellular solids. Novel tensorial mobility approach is employed for diffuse interface heat transfer. Pore scale level CFD simulation using diffuse interface lattice Boltzmann method. Validation on complex engineering type geometries show excellent agreement. Abstract: This work presents a contribution on the numerical modelling capabilities for the simulation of fluid flow and heat transfer in cellular solids – in particular we focus on open cell aluminium foams. Rather than applying one of the classical academical or commercial numerical finite volume (FV), finite difference (FD) or finite element (FE) interface tracking methods, we base our models on an interface capturing phase field method (Nestler, 2005). A coupled diffuse interface lattice Boltzmann fluid flow solver (Ettrich, 2014) and a diffuse interface heat transfer approach (Ettrich et al., 2014) are combined in view of dealing with even more convoluted geometries, incorporating the dynamics of interfaces and complex multiphysics applications. Numerical results for the combined fluid flow and heat transfer simulations in open cell metal foams are in very good agreement with experimental data (Ettrich and Martens, 2012; Ettrich et al., 2012).